La importancia de la participación de la mujer en el cumplimiento de los ODS 5 y 6, durante el periodo del Plan nacional del Buen Vivir 2013-2017 - Enríquez Pacheco, Belén Carolina (2020)
This paper deals with the challenges around access and treatment of water in Ecuador and, as central axis, the participation of women in it. The Sustainable Development Goals (SDG) that emerged in 2015 has been one of the most recognized international proposals to promote the achievement of 17 goals in different areas, including gender and environment topics, ¿is there really a progress in the compliance with the ODS 5 and 6 in the country? This research focuses on the influence of ecofeminism theory with regard to urban and rural women so that their voices have recognition in patriarchal society. Moreover, this investigation focuses on understanding how collective support can make a difference in the fulfillment of domestic chores, and how does violence or lack of education affect women to detached from their particular role as “housewives”. The investigation emphasizes on the third period of the Plan Nacional del Buen Vivir (2013-2017) where the idea of the Sumak Kawsay or "Good Living" is introduced. The purpose will be to verify whether or not this plan has beard results during this period of time and if it has made a difference in compliance with SDG 5 and 6. Key words: Environment, Water, Gender, Ecofeminism, DSG, Sumak Kawsay, PNBV